2019
DOI: 10.1038/s41467-019-11870-x
|View full text |Cite
|
Sign up to set email alerts
|

RBM3 promotes neurogenesis in a niche-dependent manner via IMP2-IGF2 signaling pathway after hypoxic-ischemic brain injury

Abstract: Hypoxic ischemia (HI) is an acute brain threat across all age groups. Therapeutic hypothermia ameliorates resulting injury in neonates but its side effects prevent routine use in adults. Hypothermia up-regulates a small protein subset that includes RNA-binding motif protein 3 (RBM3), which is neuroprotective under stressful conditions. Here we show how RBM3 stimulates neuronal differentiation and inhibits HI-induced apoptosis in the two areas of persistent adult neurogenesis, the subventricular zone (SVZ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 49 publications
0
68
0
Order By: Relevance
“…Specifically, in SH-SY5Y cells, RBM3 possesses neuroprotective effects against various neurotoxins, such as rotenone [94], 1-methyl-4-phenylpyridinium [95], nitric oxide [96], and UV irradiation-induced apoptosis [97]. Notably, RBM3 promotes neurogenesis after hypoxic-ischemic brain injury in a niche-dependent manner via IGF2BP2-IGF2 signalling [98]. Although RBM3 is a proto-oncogene (in that it facilitates cell division and attenuates apoptosis), its expression is surprisingly associated with favourable oesophageal cancer phenotype in tissue microarrays [99].…”
Section: There Are Several Novel and Reported Genes That Are Expressementioning
confidence: 99%
“…Specifically, in SH-SY5Y cells, RBM3 possesses neuroprotective effects against various neurotoxins, such as rotenone [94], 1-methyl-4-phenylpyridinium [95], nitric oxide [96], and UV irradiation-induced apoptosis [97]. Notably, RBM3 promotes neurogenesis after hypoxic-ischemic brain injury in a niche-dependent manner via IGF2BP2-IGF2 signalling [98]. Although RBM3 is a proto-oncogene (in that it facilitates cell division and attenuates apoptosis), its expression is surprisingly associated with favourable oesophageal cancer phenotype in tissue microarrays [99].…”
Section: There Are Several Novel and Reported Genes That Are Expressementioning
confidence: 99%
“…) • A single nucleotide polymorphism in NAB1 is associated with systemic lupus erythematosus, rheumatoid arthritis, systemic sclerosis, and idiopathic inflammatory myopathies (Acosta-Herrera et al, 2019) NTN1 2.09E−50, 2.32E−03 • Overexpressing Ntn1 in the mouse gut suppresses intestinal cell apoptosis and promotes tumor development (Mazelin et al, 2004) • In mice lacking the low-density lipoprotein receptor, deleting Ntn1 in macrophages attenuates atherosclerosis (van Gils et al, 2012) • In a mouse model of obesity, the hematopoietic deletion of Ntn1 enhances insulin sensitivity and decreases inflammation (Ramkhelawon et al, 2014) PAK4 2.47E−04, 9.28E−04 • Knocking down PAK4 in ovarian cancer cells prior to inoculation impedes tumor growth and dissemination in nude mice (Siu et al, 2010) • Overexpressing or depleting Pak4 in mice promotes or delays mammary cancer, respectively (Costa et al, 2019) • Growth is suppressed and invasive potential is decreased by the inhibition of PAK4 in human bladder cancer cells (D. S. Chandrashekar et al, 2020) PLA2G2A 1.56E−03, 7.11E−04 • The size and multiplicity of intestinal tumors are reduced in mice overexpressing Pla2g2a (Cormier et al, 1997) • The expression of PLA2G2A is positively correlated with survival in patients with gastric adenocarcinoma (Leung et al, 2002) • In Muc2 −/− mice, the transgenic expression of Pla2g2a suppresses intestinal tumorigenesis (Fijneman et al, 2008) PLXNB2 9.33E−40, 1.17E−03 • Inhibiting PLXNB2 suppresses the development of xenograft tumors in mice (Yu et al, 2017) • Inhibiting PLXNB2 makes prostate cancer stem cells more sensitive to chemotherapy (Li et al, 2020) • Motor sensory recovery following spinal cord injury is impaired in mice lacking Plxnb2 in myeloid cells (X. Zhou et al, 2020) POMC 1.53E−07, 9.34E−04 • Mutations in POMC cause early-onset obesity and adrenal insufficiency in humans(Krude et al, 1998) • Blocking the expression of Pomc in hypothalamic neurons causes hyperphagia and obesity in mice(Bumaschny et al, 2012) • In obese patients with defects in POMC, treatment with a melanocortin-4 receptor agonist reduces hunger and induces weight loss (Kuhnen et alexpressing aakg-2 (worm ortholog of PRKAG1) are more resistant to oxidative stress and live longer(Greer et al, 2007) • Ampk elevates cellular NAD + levels and enhances the activity of Sirt1 in mouse skeletal muscle(Canto et al, 2009) • Overexpressing AMPKα (fly ortholog of PRKAA1) in neurons induces autophagy and extends life span in Drosophila(Ulgherait et al, 2014) RBM3 6.61E−20, 2.21E−03 • Cold stress increases the expression level of RBM3 in multiple different human cell lines(Danno et al, 1997) • Overexpressing Rbm3 prevents neuronal loss and prolongs survival in Alzheimer's disease mice(Peretti et al, 2015) • In response to hypoxic ischemia, Rbm3 promotes the proliferation of neural stem/progenitor cells in the subgranular zone (X Zhu et al, 2019). …”
mentioning
confidence: 99%
“…As a newly positive regulator of SGs formation, the identification of RBM3 may have high relevance to improving the understanding of the process of SGs assembly. The promoting effect of RBM3 in SGs formation provides a novel insight into understanding the protective effect of RBM3 on brain injury ( Zhuang et al, 2017 ; Jackson et al, 2019 ; Yang et al, 2019 ; Zhu et al, 2019 ). Second, Co-IP experiments revealed that the interaction between RBM3 and G3BP1 significantly increase under OGD/R condition.…”
Section: Discussionmentioning
confidence: 99%